MEDIATION RECONSTRUCTION AS ONE OF THE ALTERNATIVE SETTLEMENT OF GIVING SIDE IN THE COURTS BASED ON JUSTICE VALUES - maria sm purba (Jurnal Pembaharuan Hukum, 2017)
AbstractMediation is one alternative form of dispute resolution. In the mediation, a win-win solution for the parties is sought. In the settlement of civil cases in the court, prioritized mediation settlement, as stipulated in Perma No. 1 Year 2008. However, the implementation of mediation in court based on Perma No. 1 Year 2008 has not been effective because of obstacles in the implementation of mediation. The constraints must be sought to resolve the efforts by reconstructing the implementation of mediation as an alternative to civil disputes in court that can provide justice for the parties.